Field testing of ICHD-3 beta criteria of periictal headaches in patients with focal epilepsy – a prospective diary study. (February 2018) - Lieba-Samal, Doris; Wöber, Christian; Waiß, Christoph; Kastiunig, Theresa; Seidl, Matthias; Mahr, Nina; Aull-Watschinger, Susanne; Pataraia, Ekaterina; Seidel, Stefan
Background: To date we are lacking prospective data for field testing of ICHD-3 beta criteria for periictal headache (PIH). Methods: Patients with focal epilepsy diagnosed by means of prolonged video-EEG monitoring completed a paper-pencil diary for three months and recorded seizures and headaches on a daily basis. According to ICHD-3 beta, we classified PIH, defined as headache present on a day with at least one seizure, as "7.6 headache related to epileptic seizure", "7.6.1 hemicrania epileptica" or "7.6.2 postictal headache". In addition, we compared the ICHD-3 beta diagnoses to the diagnoses according to ICHD-2. Results: Thirty two patients completed the diary. Data analysis included 2, 668 patient days, 300 seizures and 37 episodes of PIH. Two of these episodes (5.4%) were classified as headache related to seizure, three (8.1%) fulfilled both the criteria of headache related to seizure and hemicrania epileptica and four (10.8%) were postictal headaches. Twenty eight episodes (75.7%) did not fulfil any of the ICHD-3 beta criteria of seizure-related headaches, mostly because headache onset was before seizure onset. Applying ICHD-2 criteria allowed only one single episode of PIH to be classified as postictal headache. Discussion: Our study is the first to present prospective field testing data of the ICHD-3 beta criteria for three types of seizure-related headaches. The majority of PIH episodes do not fulfil any of these criteria. One quarter can be classified according to ICHD-3 beta, whereas purely clinical diagnosis of PIH is markedly restricted in ICHD-2 because of mandatory electroencephalographic evidence.